Early microscopic findings in preclinical inflammatory bowel disease. Issue 12 (December 2020) - Rodríguez-Lago, Iago; Ramírez, Cynthia; Merino, Olga; Azagra, Irene; Maiz, Ainara; Zapata, Eva; Higuera, Rebeca; Montalvo, Isabel; Fernández-Calderón, María; Arreba, Paz; Carrascosa, Juan; Iriarte, Ainara; et al.
Abstract: Background: The immune response involved in the pathogenesis of Inflammatory Bowel Disease (IBD) may be present years before the diagnosis, but the characteristics of the disease during the preclinical period have been scarcely investigated. Aim: To describe the microscopic findings of preclinical IBD and its relationship with the natural history of the disease. Methods: Medical records from all patients with an incidental diagnosis of IBD during a screening colonoscopy were included in this multicentric and retrospective study. We assessed 15 histologic items in the biopsy samples at diagnosis, and the Geboes score was calculated in patients with Ulcerative Colitis (UC). The main outcome was the development of gastrointestinal symptoms during follow-up. Results: We included 110 patients (79 UC, 24 Crohn's Disease (CD) and 7 with unclassified disease). In UC the most common histologic findings were acute or chronic inflammatory infiltrate and crypt epithelial polymorphs, while in CD we observed acute or chronic neutrophilic infiltrate and epithelial irregularity. Granuloma were only observed in 4% of CD patients. Crypt distortion and the infiltration of neutrophils in the epithelium were associated with a higher risk of developing symptomatic disease. Conclusions: Preclinical IBD shows specific microscopic findings and they are associated with the progression to symptomatic disease.